The Addams family [videorecording (Blu-Ray + DVD)] - Vernon, Conrad; Lieberman, Matt, 1972-; Rivinoja, Erica; Danna, Mychael; Danna, Jeff; Salter, David Ian, 1966- (Universal Pictures Home Entertainment, 2020)
The eccentrically macabre family moves to a bland suburb where Wednesday Addams' friendship with the daughter of a hostile and conformist local reality show host exacerbates conflict between the families.